Factory simulation construction method and implementation of intelligent manufacturing - Zheng, Bin; Bai, Yan; Yang, Soo Siang; Tan, Ming Keng; Zhang, Jing Song (UiTM Cawangan Perlis, 2025)
Construction methods and implementation of factory simulation of intelligent manufacturing discusses the key construction methods and realization ways of factory simulation in the field of intelligent manufacturing. As the core of the digital twin industry, it plays an important role in optimizing production and improving resource utilization. This paper expounds the construction method of factory simulation, including digital modeling, simulation parameter setting, advanced algorithm application and real-time data fusion. At the same time, it points out the challenges of model complexity and data accuracy in the simulation construction process and proposes corresponding solutions. This paper also takes Plant Simulation software as an example to analyze the implementation steps of factory simulation, such as model building, parameter configuration and process planning, emphasizing its value in optimizing factory layout, improving production process, and enhancing the scientific nature of decision-making. This paper comprehensively shows the key technical points and future development trend of factory simulation and provides theoretical support and practical guidance for the technological progress and industrial upgrading of intelligent manufacturing industry.